Rainbow Studio / Zulkarnain Jemat, Norazwin Azreen Samsudin, Ameran Daud... [et.al]. - Jemat, Zulkarnain; Samsudin, Norazwin Azreen; Daud, Ameran (Faculty of Artistic and Creative Technology, 2004)
We choose this name because people will get to know easily what kind of business that we recognize. RAINBOW STUDIO is involved in the rental of music studio for jamming. The company is located at No. 201, Blok 31, Jalan Plumbum, 7/97, Sekyen 7, 40000, Shah Alam, Selangor.